Step
*
1
2
2
2
of Lemma
add-ipoly_wf
1. n : ℤ
2. 0 < n
3. ∀p,q:iMonomial() List.
     (||p|| + ||q|| < n - 1
     
⇒ (∀i:ℕ||p||. ∀j:ℕi.  imonomial-less(p[j];p[i]))
     
⇒ (∀i:ℕ||q||. ∀j:ℕi.  imonomial-less(q[j];q[i]))
     
⇒ (↓∀i:ℕ||add-ipoly(p;q)||. ∀j:ℕi.  imonomial-less(add-ipoly(p;q)[j];add-ipoly(p;q)[i])))
4. u : iMonomial()
5. v : iMonomial() List
6. u1 : iMonomial()
7. v1 : iMonomial() List
8. ||[u / v]|| + ||[u1 / v1]|| < n
9. ∀i:ℕ||[u / v]||. ∀j:ℕi.  imonomial-less([u / v][j];[u / v][i])
10. ∀i:ℕ||[u1 / v1]||. ∀j:ℕi.  imonomial-less([u1 / v1][j];[u1 / v1][i])
⊢ ↓∀i:ℕ||add-ipoly([u / v];[u1 / v1])||. ∀j:ℕi.
     imonomial-less(add-ipoly([u / v];[u1 / v1])[j];add-ipoly([u / v];[u1 / v1])[i])
BY
{ ((RecUnfold `add-ipoly` 0 THEN Reduce 0)
   THEN (Subst' null(<u, v>) ~ ff 0 THENA Auto)
   THEN (Subst' null(<u1, v1>) ~ ff 0 THENA Auto)
   THEN Reduce 0
   THEN (BoolCase ⌜imonomial-le(u;u1)⌝⋅ THENA Auto)) }
1
1. n : ℤ
2. 0 < n
3. ∀p,q:iMonomial() List.
     (||p|| + ||q|| < n - 1
     
⇒ (∀i:ℕ||p||. ∀j:ℕi.  imonomial-less(p[j];p[i]))
     
⇒ (∀i:ℕ||q||. ∀j:ℕi.  imonomial-less(q[j];q[i]))
     
⇒ (↓∀i:ℕ||add-ipoly(p;q)||. ∀j:ℕi.  imonomial-less(add-ipoly(p;q)[j];add-ipoly(p;q)[i])))
4. u : iMonomial()
5. v : iMonomial() List
6. u1 : iMonomial()
7. v1 : iMonomial() List
8. ||[u / v]|| + ||[u1 / v1]|| < n
9. ∀i:ℕ||[u / v]||. ∀j:ℕi.  imonomial-less([u / v][j];[u / v][i])
10. ∀i:ℕ||[u1 / v1]||. ∀j:ℕi.  imonomial-less([u1 / v1][j];[u1 / v1][i])
11. ↑imonomial-le(u;u1)
⊢ ↓∀i:ℕ||if imonomial-le(u1;u)
      then let x ⟵ add-ipoly(v;v1)
           in let cp,vs = u 
              in eval c = cp + (fst(u1)) in
                 if c=0 then x else [<c, vs> / x]
      else let x ⟵ add-ipoly(v;[u1 / v1])
           in [u / x]
      fi ||. ∀j:ℕi.
     imonomial-less(if imonomial-le(u1;u)
     then let x ⟵ add-ipoly(v;v1)
          in let cp,vs = u 
             in eval c = cp + (fst(u1)) in
                if c=0 then x else [<c, vs> / x]
     else let x ⟵ add-ipoly(v;[u1 / v1])
          in [u / x]
     fi [j];if imonomial-le(u1;u)
     then let x ⟵ add-ipoly(v;v1)
          in let cp,vs = u 
             in eval c = cp + (fst(u1)) in
                if c=0 then x else [<c, vs> / x]
     else let x ⟵ add-ipoly(v;[u1 / v1])
          in [u / x]
     fi [i])
2
1. n : ℤ
2. 0 < n
3. ∀p,q:iMonomial() List.
     (||p|| + ||q|| < n - 1
     
⇒ (∀i:ℕ||p||. ∀j:ℕi.  imonomial-less(p[j];p[i]))
     
⇒ (∀i:ℕ||q||. ∀j:ℕi.  imonomial-less(q[j];q[i]))
     
⇒ (↓∀i:ℕ||add-ipoly(p;q)||. ∀j:ℕi.  imonomial-less(add-ipoly(p;q)[j];add-ipoly(p;q)[i])))
4. u : iMonomial()
5. v : iMonomial() List
6. u1 : iMonomial()
7. ¬↑imonomial-le(u;u1)
8. v1 : iMonomial() List
9. ||[u / v]|| + ||[u1 / v1]|| < n
10. ∀i:ℕ||[u / v]||. ∀j:ℕi.  imonomial-less([u / v][j];[u / v][i])
11. ∀i:ℕ||[u1 / v1]||. ∀j:ℕi.  imonomial-less([u1 / v1][j];[u1 / v1][i])
⊢ ↓∀i:ℕ||let x ⟵ add-ipoly([u / v];v1)
         in [u1 / x]||. ∀j:ℕi.
     imonomial-less(let x ⟵ add-ipoly([u / v];v1)
                    in [u1 / x][j];let x ⟵ add-ipoly([u / v];v1)
                                   in [u1 / x][i])
Latex:
Latex:
1.  n  :  \mBbbZ{}
2.  0  <  n
3.  \mforall{}p,q:iMonomial()  List.
          (||p||  +  ||q||  <  n  -  1
          {}\mRightarrow{}  (\mforall{}i:\mBbbN{}||p||.  \mforall{}j:\mBbbN{}i.    imonomial-less(p[j];p[i]))
          {}\mRightarrow{}  (\mforall{}i:\mBbbN{}||q||.  \mforall{}j:\mBbbN{}i.    imonomial-less(q[j];q[i]))
          {}\mRightarrow{}  (\mdownarrow{}\mforall{}i:\mBbbN{}||add-ipoly(p;q)||.  \mforall{}j:\mBbbN{}i.    imonomial-less(add-ipoly(p;q)[j];add-ipoly(p;q)[i])))
4.  u  :  iMonomial()
5.  v  :  iMonomial()  List
6.  u1  :  iMonomial()
7.  v1  :  iMonomial()  List
8.  ||[u  /  v]||  +  ||[u1  /  v1]||  <  n
9.  \mforall{}i:\mBbbN{}||[u  /  v]||.  \mforall{}j:\mBbbN{}i.    imonomial-less([u  /  v][j];[u  /  v][i])
10.  \mforall{}i:\mBbbN{}||[u1  /  v1]||.  \mforall{}j:\mBbbN{}i.    imonomial-less([u1  /  v1][j];[u1  /  v1][i])
\mvdash{}  \mdownarrow{}\mforall{}i:\mBbbN{}||add-ipoly([u  /  v];[u1  /  v1])||.  \mforall{}j:\mBbbN{}i.
          imonomial-less(add-ipoly([u  /  v];[u1  /  v1])[j];add-ipoly([u  /  v];[u1  /  v1])[i])
By
Latex:
((RecUnfold  `add-ipoly`  0  THEN  Reduce  0)
  THEN  (Subst'  null(<u,  v>)  \msim{}  ff  0  THENA  Auto)
  THEN  (Subst'  null(<u1,  v1>)  \msim{}  ff  0  THENA  Auto)
  THEN  Reduce  0
  THEN  (BoolCase  \mkleeneopen{}imonomial-le(u;u1)\mkleeneclose{}\mcdot{}  THENA  Auto))
Home
Index